2020
DOI: 10.1111/psyg.12613
|View full text |Cite
|
Sign up to set email alerts
|

Mental health symptoms, spiritual well‐being and meaning in life among older adults living in nursing homes and community dwellings

Abstract: Background: Ageing is a process involving physical, social, psychological, spiritual and cultural changes. The elderly's personal characteristics may change, and the place where they live can lead to differences in their individual life expectations. Nursing home or community dwelling, where the elderly live can affect their psychological and spiritual well-being and their search for meaning in life. This study aimed to determine mental health symptoms, spiritual well-being and meaning in life among older adul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 33 publications
1
5
0
2
Order By: Relevance
“…Meanwhile, the meaning of life, self, and people around scores of the female elderly were higher than those of male elderly in urban areas. In rural and urban areas, the dimensions of spirituality and attitudes toward death were also affected by age, educational status, marital status, and health condition, which is supported by previous studies (Aydın et al, 2020 ; Garbaccio et al, 2018 ; Hirakawa et al, 2019 ; Kwak, 2020 ; Liu et al, 2015 ; MacLeod et al, 2019 ; Ohrnberger et al, 2017 ; Rababa et al, 2021 ; Stokes & Moorman, 2018 ; Su et al, 2017 ; Zadworna-Cieslak, 2020 ; Zhou et al, 2018 ).…”
Section: Discussionsupporting
confidence: 83%
“…Meanwhile, the meaning of life, self, and people around scores of the female elderly were higher than those of male elderly in urban areas. In rural and urban areas, the dimensions of spirituality and attitudes toward death were also affected by age, educational status, marital status, and health condition, which is supported by previous studies (Aydın et al, 2020 ; Garbaccio et al, 2018 ; Hirakawa et al, 2019 ; Kwak, 2020 ; Liu et al, 2015 ; MacLeod et al, 2019 ; Ohrnberger et al, 2017 ; Rababa et al, 2021 ; Stokes & Moorman, 2018 ; Su et al, 2017 ; Zadworna-Cieslak, 2020 ; Zhou et al, 2018 ).…”
Section: Discussionsupporting
confidence: 83%
“…Retomando el cuidado espiritual e importancia de su abordaje desde la enfermería y los profesionales de salud, en Turquía se evidenció que la conciencia de los trabajadores de salud es relevante en la asistencia de los adultos mayores para ayudarles en la comprensión de los cambios por lo que atraviesan y la búsqueda del significado de su existencia por esto es imprescindible la formación de dichos trabajadores de salud 29 , por otra parte los proveedores de atención médica son los directos responsables de hacer que la situación sea apropiada para el desarrollo espiritual para el fortalecimiento de la autoestima y dignidad 30 , en el mismo sentido la provisión de atención espiritual por parte de enfermeros y médicos es considerada como un factor que mejora la salud espiritual de los adultos mayores 31 .…”
Section: Discussionunclassified
“…Very recent studies in different parts of the world and with different groups and populations have shown the association of spiritual health with the reduction of symptoms of depression. As an example of these studies, there are those carried out among older adults in Turkey living in nursing homes and community housing (Aydin et al, 2020), patients diagnosed with breast cancer (Soleimani et al, 2020) and hospitalized with serious illnesses in Iranian medical centers (Bashar et al, 2018;Khademvatani et al, 2015), adults from the general American (Roeback III, 2020) and Korean population (Fukai et al, 2020), adults living in Spain during the pandemic of Covid-19 (González-Sanguino et al, 2020), American Methodist clergy (Milstein et al, 2020) and patients with chronic orthopedic diseases in China (Weng et al, 2021). Likewise, significant negative correlations were found between spiritual health and anxiety in studies already cited (Aydin et al, 2020;González-Sanguino et al, 2020;Soleimani et al, 2020;Weng et al, 2021) and in other Iranian samples, from hospitalized coronary patients (Hedayati et al, 2016;Khademvatani et al, 2015), from nurses, midwives and nursing students (Rahimi et al, 2017) and elderly from the general population (Solaimanizadeh et al, 2020).…”
Section: Spiritual Health and Symptoms Of Depression And Anxietymentioning
confidence: 99%